Spinal mobility in children with diabetes and factors, which influence it - O. Ye. Pashkova; K. P. Lysenko (Patologìâ)
Aim of study: to evaluate spine mobility, as an integral marker of joint mobility, according to the duration of the disease and provision of vitamin D in children with diabetes.